The Influence of Technology on The Psychology of Child Development in The Perspective of Islamic Education - Aprido, Mohamad; Muzaki, Ahmad; Utomo, Wahyu; Abidin, Zaenal (Kirana Publisher (KNPub), 2025)
The digital era has transformed parenting patterns, encouraging the need to integrate Islamic values in digital parenting practices. This study analyzes the concept of digital parenting through the lens of tarbiyah islamiyah and the impact of technology on child development psychology with a qualitative approach through library research. Content analysis was carried out on the literature of Islamic education and contemporary psychology to answer three research questions: (1) What is the representation of the concept of digital parenting and tarbiyah islamiyah in Islamic literature? (2) What is the impact of digital technology on children's cognitive, emotional, and spiritual development? (3) How can the principle of tarbiyah islamiyah be implemented in digital parenting? The findings reveal that digital parenting in Islam must be based on the concepts of muraqabah, tawazun, and ihsan, while technology risks causing developmental disruptions if not strictly supervised. This study offers an Islamic Digital Parenting framework that combines developmental psychology with Islamic values, emphasizing screen time restrictions, moral media literacy, and parental examples. Research recommendations include socialization of this model to parents and educational institutions, as well as the development of Islamic parenting curricula in the digital era.